Rainforest conversion in Central Sulawesi, Indonesia: recent development and consequences for river discharge and water resources - Leemhuis, Constanze; Erasmi, Stefan; Twele, André; Kreilein, Heinrich; Oltchev, Alexander; Gerold, Gerhard (ERDKUNDE, 2007)
The present land cover of humid tropical catchment areas mainly regulates the flow of vapour to the atmosphere. Therefore land use decisions play an important role for the water balance of a tropical catchment. Studies that relate land cover changes with river discharge changes for humid tropical catchment areas at the mesoscale level are rare. This article applies an integrated remote sensing and hydrological modelling approach to analyse the impact of land cover changes on the water resources of a mesoscale humid tropical catchment. First, a change detection analysis of Landsat/ETM+ satellite images was carried out to quantify land cover changes of the mesoscale Gumbasa River catchment in Central Sulawesi, Indonesia. Thereafter the distributed hydrological model WASIM-ETH was calibrated and validated for the current Landsat/ETM+ scene. The historical Landsat/ETM+ scene was integrated for the hydrological model application as a historical land cover scenario. Further hypothetical total-change scenarios were carried out. The results of the hydrological model scenario application clearly demonstrate a strong relationship between deforestation rates and increasing discharge variability. Especially a significant increase of high water discharges was simulated for the applied scenarios. With regard to the high deforestation rates of the research catchment, one can expect further changes of the water balance.